Technology for Training Creative Graduates in Engineering Bachelor’s Programs - A. P. Isaev; L. V. Plotnikov (Высшее образование в России)
This article is devoted to technologies of engineering education that produce the most in-demand professional qualities of graduates from Bachelor’s programs. A review of studies about introducing innovations to improve the educational process in practice-oriented Bachelor’s studies is carried out. The advantages and limitations of project-based and problem-based learning technologies are defined. The work presents the experience of developing and applying a unique teaching technology based on the integration of problemand project-based training approaches, designed to enhance the creativity of the study process in engineering Bachelor’s programs. It is described with a focus on the mechanisms for the integrated use of the advantages of methods of problemand project-based training in the formation of the professional competencies required for an engineer’s innovative activity in the development of a new product project. The data from an empirical study have been considered; they allow us to substantiate the conclusion that the integration of projectand problem-based learning in the form of a holistic technology is effective for developing students’ creative capacities.